A MAC protocol for the mixed scenario of omnidirectional and directional nodes in an ad hoc network. (3rd June 2013) - Alam, Md. Nasre; Hussain, Md. Asdaque; Khan, Pervez; Kim, Baek‐Hyun; Kwak, Kyung Sup
SUMMARY In ad hoc networks, directional antennas offer many benefits compared with classical omnidirectional antennas. Those include significant increases in spatial reuse, coverage range, and subsequently network capacity as a whole. Most of the proposed directional medium access control methods assume that all the nodes in the network have homogeneous antenna types. However, it is quite unusual that a sudden change will occur, and every laptop, palmtop, computer, and other similar device will be turned into a directional antenna holding device. There will always be a possibility of heterogeneous antenna used in the deployed nodes of the network. In this paper, we have proposed a medium access control protocol that deals with the new challenges introduced into heterogeneous networks in the form of deaf and hidden node problems. Using Optimized Network Engineering Tools 16.0, we have simulated three ad hoc network scenarios. These scenarios have different ratios of omnidirectional and directional nodes. We evaluated the performance of these scenarios by varying the ratio. We found that when we increase the directional nodes in the network, the performance increases. Copyright © 2013 John Wiley & Sons, Ltd.